The Influence of Professionalism and Auditor Competency Towards Quality Audit Internal (Study on the Department of Housing, Residential Areas and Land Affairs Bandung Regency) - Noor, Julfan Herliansyah; Ainunnisa, Rarassatika; Arifin, Farid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This Jurnal entitled